Manajemen Pendidikan Islam Terpadu Dalam Membentuk Karakter Peserta Didik - Mahendra Pudjiono (THE JOER: Journal Of Education Research, 2022)
The character of students is a characteristic of the behavior of a student. Character can be established if there is a result of student interaction with the school environment. Students are said to be good if the person has ethical morals that become a reference for the person to be able to form a better character. The focus of the research in this study is, 1) How is the implementation of integrated Islamic education management in MA Sabilul Muttaqin? 2 What are the implications of integrated Islamic education management in shaping the character of students at MA Sabilul Muttaqin?. While the objectives of this study are 1) to analyze the implementation of integrated Islamic education management at MA Sabilul Muttaqin. 2) Analyzing the implications of integrated Islamic education management in shaping the character of students at MA Sabilul Muttaqin.. The type of research used is qualitative (qualitative research) and the research approach is a case study. Then to determine the level of validity is the source of the data obtained from the provision of information by the principal, waka student, teachers, and education staff as well as in the form of documents written materials. The results of this study are, the implementation of integrated Islamic education management at MA Sabilul Muttaqin Pungging Mojokerto is good if it meets the indicators, namely: 1) there is an encouragement for the necessities of life for religious knowledge and general science, 2) Islamic education in Islam by way of circumventing learning resources and related matters to achieve the goals of Islamic education effectively and efficiently. The implications of integrated Islamic education management in shaping the character of students at MA Sabilul Muttaqin Pungging Mojokerto, namely: 1) the benefits are great where students in the management are combined between religious subjects and general subjects, 2) With integrated Islamic education can provide motivation in forming noble character students.